Spirit kebersihan masyarakat Penglipuran Bali: Konvergensi nilai keberagamaan dan kearifan lokal - Fathorrahman; Muh. Syamsuddin (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
This paper explains the spirit of cleanliness which is constructed in the life of the people of Penglipuran Bali. By synergizing local wisdom and religious spirit, the Penglipuran community manifests a culture of clean behavior and good environmental care. Various religious concepts that refer to the Hindu belief system, Penglipuran people derive transcendental concepts such as Tri Hita Karana in their daily lives and in their sphere of life. This paper poses two important questions as the basis for the analysis of the problem. First, What is the concept of environmental cleanliness according to the Penglipuran community. Second, is there a meeting point for the value of local wisdom and the spirit of religion in guiding public awareness in realizing environmental cleanliness. The writer analyzed this problem using a sociological approach in the perspective of interpretive understanding. From the research process carried out, the authors found that the meaning of cleanliness constructed by the Penglipuran community is based on value of religiousity. Through Hindu teachings that emphasize the concept of Tri Hita Karana, the people derive it from various spheres of their lives in protecting the environment and building a culture of clean behavior. On the other hand, Penglipuran community also uses local wisdom as a way of looking at, how to behave, and how to act in maintaining the cleanliness and beuty of the Penglipuran environment.